Mechanisms of Change in Mindfulness-Based Cognitive Therapy in Adults With ADHD. Issue 9 (July 2021) - Geurts, Dirk E.M.; Schellekens, Melanie P. J.; Janssen, Lotte; Speckens, Anne E. M.
Objective: Mindfulness-based cognitive therapy (MBCT) has been demonstrated to be effective in adults with ADHD. The aim of the current study was to examine its possible working mechanisms.Method: In the context of an randomized controlled trial (RCT), MBCT + TAU (treatment as usual) ( n = 43) versus TAU ( n = 51), we used mediation analyses to examine whether reduction of clinician-rated ADHD symptoms and improvement of positive mental health at 6-month follow-up had been mediated by change in mindfulness skills, self-compassion, and executive functioning over the course of MBCT.Results: Increase of self-compassion mediated improvement of positive mental health at 6-month follow-up. Improvement of mindfulness skills or self-compassion did not mediate the reduction in ADHD symptoms. Additional analyses suggest that self-reported inhibition did.Conclusion: The effect of MBCT on ADHD symptoms and positive mental health thus occurred via different mechanisms of change, that is, by improvements in inhibition and self-compassion, respectively.